Investigations on Herbicides in Field Crops in Libya: I.Effect of Application Methods of Herbicides on Growth, Yield, Yield Components, and Weeds in Maize (Zea mays L.) - SHAALAN, M. I.; SOROUR, F. A.; EL-SHARKAWY, M. A. (The Libyan Journal of Agriculture, 2023)
The combined effect of three herbicides (AC92,553, Trifluralin, and Dacthal) and three application methods (preplanting soil-incorporated, preemergence, and postemergence) on growth, yield, yield components, and weeds in maize (Zea mays L.) was investigated under conditions of Tripoli, Libya, in the 1974 summer season. The preplanting method generally caused a significant detrimental reduction in the percentage of seedling emergence. The pre-and postemergence applications caused slight reductions in this percentage. The three herbicides were similar in their effect upon such percentage. The preplanting method caused a significant reduction in the seedling fresh weight. The herbicides exerted similar effect on this weight. The least seedling height was obtained with the preplanting treatment and the highest with the control. Several summer annual and perennial weeds showed different modifications in growth as affected by the treatments. In general, the preplanting and preemergence methods significantly reduced the fresh weight of weeds. The herbicides reduced this weight in comparison with the untreated plots. Generally, the preemergence and postemergence treatments resulted in superior maize yields over the preplanting method. AC92,553 and Trifluralin gave nonsignificant higher yields of ears and grain than that of Dacthal. For example, the grain yield values corresponding to these herbicides were 1.88, 1.99, and 1.61 kg per plot. The lowest significant mean number of ears per plot (3.24) was that of the preplanting method. The length of husked ears and the 1,000-grain weight were not significantly influenced by either the herbicides or the application methods. According to these results, the following conclusions may be drawn: 1. The recommended application method for AC92,553 and Trifluralin(preplanting soil-incorporated) proved to be injurious to maize growth, yield, and yield components. It may be invalid for weed control in maize under Tripoli conditions. 2. AC92,553 and Trifluralin might be applied for weed control in maize under Tripoli conditions as preemergence and postemergence treatments. 3. Dacthal may not be suitable because it showed inferior results under the present conditions. 4. Further studies are required to examine the effect of different concentrations of AC92.553 and Trifluralin beside the recommended rates for a satisfactory weed control in maize fields under the Libyan conditions.